2022
DOI: 10.1021/acssuschemeng.2c02186
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Ammonium Chloride Salts for Efficient Chlorine Storage at Ambient Conditions

Abstract: Herein, we report the use of alkyl ammonium chloride salts as safe and sustainable chlorine storage media. The most promising candidate, [NEt3Me]­Cl, stores up to 0.79 kg chlorine/kg storage material, is readily prepared, and stable against chlorination for extended times. Chlorine release can be achieved by applying heat or vacuum, or, alternatively, by the addition of water. The combination of these properties emphasizes [NEt3Me]Cl as a suitable storage medium to facilitate the flexibilization of industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 26 publications
1
23
0
8
Order By: Relevance
“…It is stable over years at room temperature and shows also no decomposition when stored in the sunlight at 50 °C. [21] [NEt 3 Me][Cl 3 ] stores up to 0.79 kg chlorine per kilogram of [NEt 3 Me]Cl, and is comparably cheap as [NEt 3 Me]Cl is industrially prepared from two base chemicals, NEt 3 and MeCl. [21] Notably, [NEt 3 Me][Cl 3 ] has a much lower vapor pressure then elemental chlorine at room temperature.…”
Section: Trichlorides As a Unique Chlorine Storagementioning
confidence: 99%
“…It is stable over years at room temperature and shows also no decomposition when stored in the sunlight at 50 °C. [21] [NEt 3 Me][Cl 3 ] stores up to 0.79 kg chlorine per kilogram of [NEt 3 Me]Cl, and is comparably cheap as [NEt 3 Me]Cl is industrially prepared from two base chemicals, NEt 3 and MeCl. [21] Notably, [NEt 3 Me][Cl 3 ] has a much lower vapor pressure then elemental chlorine at room temperature.…”
Section: Trichlorides As a Unique Chlorine Storagementioning
confidence: 99%
“…The chlorination of small molecules is a topic of major relevance both for industrial and academic research [1] . Very recently, our group in cooperation with Covestro investigated [NEt 3 Me]Cl as a practical chlorine storage medium which forms the corresponding trichloride [NEt 3 Me][Cl 3 ] by addition of chlorine [2] . More importantly, we found that [NEt 3 Me][Cl 3 ] is also a useful chlorinating agent reacting with carbon monoxide to the base chemical phosgene (COCl 2 ).…”
Section: Figurementioning
confidence: 99%
“…[1] Very recently, our group in cooperation with Covestro investigated [NEt 3 Me]Cl as a practical chlorine storage medium which forms the corresponding trichloride [NEt 3 Me][Cl 3 ] by addition of chlorine. [2] More importantly, we found that [NEt 3 Me][Cl 3 ] is also a useful chlorinating agent reacting with carbon monoxide to the base chemical phosgene (COCl 2 ). Interestingly, our studies indicate that the trichloride anion in [NEt 3 Me][Cl 3 ] has a ClÀ Cl bond which is much weaker than in elemental chlorine facilitating the insertion of carbon monoxide into the ClÀ Cl bond of the trichloride.…”
mentioning
confidence: 99%
“…Die Chlorierung kleiner Moleküle ist sowohl für die industrielle als auch für die akademische Forschung von großer Bedeutung [1] . Erst kürzlich untersuchte unsere Gruppe in Zusammenarbeit mit Covestro [NEt 3 Me]Cl als praktisches Chlorspeichermedium, das durch Zugabe von Chlor das entsprechende Trichlorid [NEt 3 Me][Cl 3 ] bildet [2] . Hervorzuheben ist, dass [NEt 3 Me][Cl 3 ] auch ein nützliches Chlorierungsmittel ist, welches mit Kohlenmonoxid zu der Basischemikalie Phosgen (COCl 2 ) reagiert.…”
Section: Figureunclassified
“…[1] Erst kürzlich untersuchte unsere Gruppe in Zusammenarbeit mit Covestro [NEt 3 Me]Cl als praktisches Chlorspeichermedium, das durch Zugabe von Chlor das entsprechende Trichlorid [NEt 3 Me][Cl 3 ] bildet. [2] Hervorzuheben ist, dass [NEt 3 Me][Cl 3 ] auch ein nützliches Chlorierungsmittel ist, welches mit Kohlenmonoxid zu der Basischemikalie Phosgen (COCl 2 ) reagiert. Unsere Untersuchungen deuten darauf hin, dass das Trichloridanion in [NEt 3 Me][Cl 3 ] eine ClÀ Cl-Bindung aufweist, die viel schwächer ist, als in elementarem Chlor, was die Insertion von Kohlenmonoxid in die ClÀ Cl-Bindung des Trichlorids erleichtert.…”
unclassified